The Meaning of Dewi Sri in the Perspective of Spiritual Ecologism in the Indigenous Peoples of Kampung Naga and Kampung Cireundeu - Ulifia, Evi Fita (FISIP UIN SGD Bandung, 2024)
This research explores the cultural significance of Dewi Sri among the indigenous communities of Kampung Naga and Kampung Cireundeu, focusing on the similarities and differences in her essence as well as the relationship between these beliefs and Ecofeminism. Conducted in Tasikmalaya Regency and Cimahi, the study employed an anthropological approach with a comparative method to analyze religious practices and ancestral values. Findings revealed that both communities regard